Effects of mobile mindfulness training on mental health of employees: A CONSORT-compliant pilot randomized controlled trial. Issue 35 (2nd September 2022) - Yoon, Seok-In; Lee, Seung-Il; Suh, Hyo-Weon; Chung, Sun-Yong; Kim, Jong Woo
Abstract : Background: Employee stress and well-being affect organizational efficiency and productivity, as well as physical and psychological health of employees. Mindfulness is believed to reduce stress, prevent diseases, and promote well-being. Mindfulness has been used as the main component of various smartphone-based healthcare applications. Previous studies have suggested that mindfulness applications have a positive effect on employee stress and mental health. However, relatively few randomized controlled trials have examined the effectiveness of mindfulness applications on employees. This study aims to evaluate whether mobile mindfulness training (MMT) as a stress self-management tool improves employees' perceived stress, subjective well-being, and Mibyeong, a condition that is not a disease but shows obvious health abnormalities. Methods: Participants were recruited through advertisements displayed at 3 workplaces, including a patent attorney's office, a construction company, and a public relations firm. A total of 45 employees were randomly assigned to 1 of 2 groups: the MMT group (Group A) receiving smartphone application-based mindfulness training, and a wait-list control (WLC) group (Group B), who received no intervention. Group A employees conducted MMT following daily and event guidelines for 4 weeks. In contrast, Group B employees did not receive any intervention in that time. The outcome variables were perceived stress, subjective well-being, and Mibyeong. Surveys were conducted at baseline, post-intervention, and follow-up (fourth week post-intervention). Results: Demographic characteristics and baseline assessments were not significantly different between the 2 groups. The results of this study revealed that subjective well-being and Mibyeong were significantly improved in the MMT group compared with the WLC group. Moreover, this improvement was maintained up to at least 4 weeks later. However, perceived stress was not significantly reduced in the MMT group compared to the WLC group. Conclusion: Four weeks of MMT improved the subjective well-being and Mibyeong of employees. However, further studies are required to investigate the effect of MMT on other areas of mental health.